Aging and social assistance policy: contradictions and challenges in basic social protection actions for the elderly (Research, Society and Development, 2022)
The proposed study is of a bibliographic nature, based on a literature review on the proposed thematic field. The results of the theoretical review indicate that: a) aging in capitalist society, and especially in Brazil, is little faced by the State/society, given the deep social inequality that marks the socioeconomic development experienced by the majority of the population; b) In Brazil, the constitution of a social protection system involved two great historical landmarks: the first period, after 1930, can be considered as the initial phase of the formation of the system with the recognition of social rights; the second milestone is located after the 1988’s Constitution, when the standard of social protection was expanded with the incorporation of the social security perspective; and, finally, c) by the prevalence of the offer of private services, especially in health and social security, denying the working class the enjoyment of socially produced wealth, reflecting more negatively on the elderly segment.